1993
DOI: 10.1381/096089293765559142
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in the Morbidly Obese

Abstract: Although vitamin D deficiency has been well-documented following gastric bypass surgery, there are few studies of vitamin D status in the non-operative morbidly obese patient. We examined 25-hydroxyvitamin D (25-OHD) levels in 60 morbidly obese pre-operative females; 62% of them had 25-OHD levels below normal range (16-74 ng/ml) which were not associated with reductions in serum calcium or phosphorus, liver or kidney dysfunction, and were not significantly correlated to patients' age. However, 25-OHD levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
58
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(75 citation statements)
references
References 0 publications
12
58
0
5
Order By: Relevance
“…4,5,19,[48][49][50][51][52] The high prevalence of low VD levels in obesity is proposed to be due to volumetric dilution in obesity, as the volume of distribution of VD increases with increased body weight. 23 Our study aimed to elucidate whether low plasma 25OHD levels in obesity could be further explained by an altered VD metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,19,[48][49][50][51][52] The high prevalence of low VD levels in obesity is proposed to be due to volumetric dilution in obesity, as the volume of distribution of VD increases with increased body weight. 23 Our study aimed to elucidate whether low plasma 25OHD levels in obesity could be further explained by an altered VD metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 The levels of serum 1,25-dihydroxyvitamin D (1,25(OH) 2 D) were elevated, whereas 25-hydroxyvitamin D (25(OH)D) levels were reduced in morbidly obese patients. 12,14,15 In addition, the levels of serum vitamin D metabolites inversely correlate with fat mass 12,16 and body mass index (BMI). 16 Therefore, DBP, playing an important role in the vitamin D endocrine system by binding with 25(OH)D and 1,25(OH) 2 D and regulating their in vivo levels and functions, 17,18 may also influence the obesity susceptibility in the human populations.…”
Section: Introductionmentioning
confidence: 99%
“…These associations have been described by several authors, both in obese and non-obese patients [8,10,11,16,[18][19][20][21][22][23][24][25][26].…”
Section: Resultsmentioning
confidence: 69%
“…Other studies have reported vitamin D deficiencies in obese patients ranging from 41% to 93.8% [6,[10][11][12][13][14][15][16][17]. This wide range may be partly due to the differences in definition of vitamin D deficiency (Table 3).…”
Section: Resultsmentioning
confidence: 98%